(untitled) (Bioscience Journal, 2022)
Photosystem-inhibiting herbicides, such as diquat, act by inducing oxidative stress. However, oxidative damage impairs translocation, resulting in regrowth of the plants. The aim was to evaluate the effectiveness of diquat in controlling the growth of sourgrass exposed to different periods of darkness after application of the herbicide, as well as to evaluate the photosynthetic activity and the production of reactive oxygen species. Two experiments (field and greenhouse) were conducted by applying diquat (200 g a.i. ha-1) on sourgrass plants at the 3 to 4 tiller stage. The treated plants were subjected to different periods of darkness after diquat application (0, 1, 2, 3, 4, 5, and 6 h), in addition to the control treatment without any application. Growth inhibition and mass evaluations of the sourgrass plants were performed in both experiments, whereas photosynthetic activity and H2O2 accumulation in the leaves were evaluated in the greenhouse experiment. The results showed an increase in the sourgrass growth inhibition with an increase in the period of darkness after application. There was a need for a minimum of 6 h of darkness after diquat application to fully inhibit growth (100%) of the sourgrass, whereas plants that remained in the sun since application exhibited less than 50% inhibition. The increase in the period of darkness after diquat application resulted in a reduction in photosynthetic activity and, consequently, lower accumulation of H2O2. Thus, the maintenance of sourgrass in the dark for at least 6 h enables total control of the growth of the plants, preventing regrowth.